2006
DOI: 10.1007/s00425-006-0222-3
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the photoperiod on redox regulation and stress responses in Arabidopsis thaliana L. (Heynh.) plants under long- and short-day conditions

Abstract: Arabidopsis thaliana L. (Heynh.) plants were grown in low light (150 micromol photons m(-2) s(-1) and 20 degrees C) either in short days (7.5 h photoperiod) or long days (16 h photoperiod), and then transferred into high light and low temperature (350-800 micromol photons m(-2) s(-1) at 12 degrees C). Plants grown in short days responded with a rapid increase in NADP-malate dehydrogenase (EC 1.1.1.82) activation state. However, persisting overreduction revealed a new level of regulation of the malate valve. Ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
50
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 43 publications
5
50
0
1
Order By: Relevance
“…When low lightgrown plants under a short-day photoperiod (7.5 h photoperiod) were transferred to high light, both the level of transcript and protein for NADP-malate-dehydrogenase increased (29). This was not observed when low light-grown plants under a long photoperiod (16 h) were switched to high light.…”
Section: Response To Moderate Light Intensitiesmentioning
confidence: 64%
“…When low lightgrown plants under a short-day photoperiod (7.5 h photoperiod) were transferred to high light, both the level of transcript and protein for NADP-malate-dehydrogenase increased (29). This was not observed when low light-grown plants under a long photoperiod (16 h) were switched to high light.…”
Section: Response To Moderate Light Intensitiesmentioning
confidence: 64%
“…The up-regulation of MDH has also been reported in different plant species under several stresses [22] including herbicides [13]. It has been hypothesized that an alteration in the chloroplast redox state caused by abiotic stresses is responsible for the release of redox signals, which in turn activate the transcription of several nuclear-encoded genes, among them NADP-MDH [22]. In addition, recently it has been revealed that a glucose catabolism associated enzyme such as MDH was markedly increased in young poplar leaves following exposure to ozone, suggesting that glucose catabolism could partly be due to a need for energy and reducing power for detoxification and the repair of damage caused by oxidative molecules [7].…”
Section: Energy and Metabolism-related Proteinsmentioning
confidence: 97%
“…We identified an up-regulated MDH from both the herbicide-treated samples. The up-regulation of MDH has also been reported in different plant species under several stresses [22] including herbicides [13]. It has been hypothesized that an alteration in the chloroplast redox state caused by abiotic stresses is responsible for the release of redox signals, which in turn activate the transcription of several nuclear-encoded genes, among them NADP-MDH [22].…”
Section: Energy and Metabolism-related Proteinsmentioning
confidence: 98%
“…These characteristics position RE in a regulatory network, which seems to functionally interconnect photoperiodic growth, amino acid homoeostasis and ROS signalling in Arabidopsis leaves [48,50,51]. Indeed, the photoperiod is emerging as a key environmental factor that modulates plant responses to organellar ROS signals [2,22,48,[52][53][54][55][56].…”
Section: Interplay Between Apoplastic and Chloroplasticmentioning
confidence: 99%